The Effects of Eight Weeks’ Very Low-Calorie Ketogenic Diet (VLCKD) on Liver Health in Subjects Affected by Overweight and Obesity - Rinaldi, Roberta; De Nucci, Sara; Castellana, Fabio; Di Chito, Martina; Giannuzzi, Vito; Shahini, Endrit; Zupo, Roberta; Lampignano, Luisa; Piazzolla, Giuseppina; Triggiani, Vincenzo; Cozzolongo, Raffaele; Giannelli, Gianluigi; et al. (Nutrients, 2023)
Very low-calorie ketogenic diets (VLCKD) are widely employed in successful weight-loss strategies. Herein, we evaluated the efficacy and safety of a VLCKD on non-alcoholic fatty liver disease (NAFLD) and parameters commonly associated with this condition in overweight and obese subjects who did not take any drugs. This prospective, real-life study included thirty-three participants who followed a VLCKD for 8 weeks. NAFLD was diagnosed using transient elastography (FibroScan). Data on anthropometric measurements, bioimpedance analysis, and biochemical assays were gathered both before and after the dietary intervention. BMI (kg/m2) (from 33.84 ± 6.55 to 30.89 ± 6.38, p < 0.01), waist circumference (cm) (from 106.67 ± 15.51 to 98.64 ± 16.21, p < 0.01), and fat mass (Kg) (from 38.47 ± 12.59 to 30.98 ± 12.39, p < 0.01) were significantly lower after VLCKD. CAP (db/m), the FibroScan parameter quantifying fatty liver accumulation, showed a significant reduction after VLCKD (from 266.61 ± 67.96 to 223 ± 64.19, p < 0.01). After VLCKD, the fatty liver index (FLI), a benchmark of steatosis, also revealed a significant decline (from 62.82 ± 27.46 to 44.09 ± 31.24, p < 0.01). Moreover, fasting blood glucose, insulin, triglycerides, total cholesterol, LDL-cholesterol, ALT, γGT, and FT3 blood concentrations, as well as insulin resistance (quantified by HOMAIR) and systolic and diastolic blood pressure levels, were significantly lower after VLCKD (p < 0.01 for all the parameters). By contrast, HDL-cholesterol, 25 (OH) vitamin D, and FT4 blood concentrations were higher after VLCKD (p < 0.01 for all parameters). The variation (δ) of CAP after VLCKD did not show a correlation with the δ of any other parameter investigated in this study. We conclude that VLCKD is a helpful approach for NAFLD independent of changes in factors commonly associated with NAFLD (obesity, fat mass, insulin resistance, lipids, and blood pressure) as well as vitamin D and thyroid hormone levels.